SQRAR: A model of coursebook evaluation - Sukarno, Sukarno (Universitas Ahmad Dahlan, 2024)
Coursebooks have become the most prominent English learning materials, especially in formal education. Therefore, recursive evaluation should be conducted to adjust the coursebook based on the current needs and learning goals. Moreover, dynamic evaluation brings interaction or mediation with a genuine act of teaching to make the evaluation more meaningful and substantial. However, limited resources are available, especially the ones that could help the teacher evaluate vivid steps dynamically. This study fulfills the need for a coursebook, especially ELT, evaluation method by following the research and development design proposed initially by Dick and Carey that many experts have simplified. The design was constructed from a sequence of steps, namely ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Thirty participants conducted an evaluation phase based on the product trial design, followed by a Focus Group Discussion (FGD). The data were gathered using a questionnaire and the interview guidelines. The instruments were developed based on the ideal coursebook criteria. They are shaped in quantitative and qualitative forms and analyzed using Creswell’s data analysis technique. Thus, a set of evaluation methods was designed: SQRAR (Survey, Question, Read, Analyse, and Recommend). The design benefits the teachers by allowing them to evaluate the coursebook systematically and effectively. Survey results demonstrate strong consensus among English teachers, advocating for urgent development of such evaluation models. Implementation of the SQRAR model involves detailed stages emphasizing thorough evaluation and constructive feedback, with micro and macro evaluation options discussed. The model ensures comprehensive evaluation, consistency, and alignment with learning objectives and provides clear recommendations for coursebook improvement.